RENCANA PENGELOLAAN TAMAN HUTAN KOTA PENJARINGAN, JAKARTA UTARA - Merrilin Lauren; Sylvie Wirawati; Liong Ju Tjung (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2021)
The procurement of green open space is one of the important things for the balance of the ecosystem for urban residents. One of the green open spaces in Jakarta which also has a function as a water catchment area in the northern part of Jakarta is the Penjaringan City Forest Park. However, the utilization of the Penjaringan City Forest Park has not been optimal with various management problems that exist in the park, so this research was conducted to identify the physical conditions and potentials and problems in the park by using location analysis, attractiveness analysis, facilities and infrastructure analysis, best practices analysis, as well as using the visitor's point of view, namely the perception and preference of visitors to management in evaluating management at the Penjaringan City Forest Park. From the results of the evaluation, a management plan was prepared which was used as a proposed management plan for the manager of the Penjaringan City Forest Park, North Jakarta. Keywords: Management; Planning; Urban Forest Park.AbstrakPengadaan ruang terbuka hijau menjadi salah satu hal yang penting bagi keseimbangan ekosistem bagi warga perkotaan. Salah satu ruang terbuka hijau di jakarta yang juga memiliki fungsi sebagai ruang resapan air di bagian utara jakarta yaitu Taman Hutan Kota Penjaringan. Namun pemanfaatan Taman Hutan Kota Penjaringan belum optimal dengan masih dapat dijumpai berbagai permasalahan pengelolaan yang ada pada taman tersebut sehingga penelitian ini bertujuan untuk mengetahui kondisi fisik serta potensi dan masalah pada taman dengan menggunakan analisis lokasi, analis daya tarik, analisis sarana dan prasarana, analisis best practices, serta menggunakan sudut pandang pengunjung yaitu persepsi dan preferensi pengunjung terhadap pengelolaan dalam melakukan evaluasi pengelolaan di Taman Hutan Kota Penjaringan. Dari hasil evaluasi yang ada dilakukan penyusunan rencana pengelolaan yang dijadikan usulan rencana pengelolaan bagi pengelola Taman Hutan Kota Penjaringan, Jakarta Utara.